H2S in Critical Illness—A New Horizon for Sodium Thiosulfate? - Tamara Merz (Biomolecules, 2022)
Ever since the discovery of endogenous H2S and the identification of its cytoprotective properties, efforts have been made to develop strategies to use H2S as a therapeutic agent. The ability of H2S to regulate vascular tone, inflammation, oxidative stress, and apoptosis might be particularly useful in the therapeutic management of critical illness. However, neither the inhalation of gaseous H2S, nor the administration of inorganic H2S-releasing salts or slow-releasing H2S-donors are feasible for clinical use. Na2S2O3 is a clinically approved compound with a good safety profile and is able to release H2S, in particular under hypoxic conditions. Pre-clinical studies show promise for Na2S2O3 in the acute management of critical illness. A current clinical trial is investigating the therapeutic potential for Na2S2O3 in myocardial infarct. Pre-eclampsia and COVID-19 pneumonia might be relevant targets for future clinical trials.